Alone in the campaign: Distrust in regulators and the coping of front‐line workers. Issue 4 (2nd April 2021) - Davidovitz, Maayan; Cohen, Nissim
Abstract: Trust is the "glue" connecting state and society and particularly relevant to how front‐line workers, who are the face of public administration vis‐à‐vis citizens, implement policy. Therefore, it is important to examine how front‐line workers' absence of trust in regulators influences the ways they cope with their clients. Our study investigates this question empirically through interviews and focus groups with 80 Israeli social service providers. Our results show that front‐line workers' distrust in regulators is a product of four factors: perceived lack of protection, clash of values, politicization in implementation processes, and regulators' "disconnection" from the field. It leads them to adopt two coping strategies: acts of self‐protection and deviation from formal policy. A further derivative is their turnover intention.